2020
DOI: 10.1177/1747493020938285
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and acute ischemic stroke – A case series from Dubai, UAE

Abstract: Normal range: D-dimer <0.5 ng/ml. b Normal range: Ferritin, 15-150 ng/ml. c Normal range: C-reactive protein <5 mg/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
(9 reference statements)
2
17
1
2
Order By: Relevance
“…To our knowledge, this is the first study that compares COVID-19 patients to non-COVID-19 patients within a prospectively collected stroke database. Similar to previous case reports and case-controlled studies, from USA ( 10 ), Iran ( 26 ), Dubai ( 27 ), France ( 28 ) and China ( 8 ), a third of our COVID-19 positive patients had severe disease, required ICU admissions, stayed longer in hospital and had fewer subjects with good outcome. These patients likely represent a subset of stroke patients in whom the viral infection likely contributed to a prothrombotic state resulting in vascular occlusions and large strokes.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, this is the first study that compares COVID-19 patients to non-COVID-19 patients within a prospectively collected stroke database. Similar to previous case reports and case-controlled studies, from USA ( 10 ), Iran ( 26 ), Dubai ( 27 ), France ( 28 ) and China ( 8 ), a third of our COVID-19 positive patients had severe disease, required ICU admissions, stayed longer in hospital and had fewer subjects with good outcome. These patients likely represent a subset of stroke patients in whom the viral infection likely contributed to a prothrombotic state resulting in vascular occlusions and large strokes.…”
Section: Discussionsupporting
confidence: 87%
“…To date there are several reports on neurological complications of COVID-19. We divided the neurological symptoms in such patients into three different groups: symptoms related to CNS involvement [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101]...…”
Section: Resultsmentioning
confidence: 99%
“… Cerebrovascular events 3 Ischemic Stroke 37 Articles [ 39 ], [ 57 ], [ 58 ], [ 60 ], [ 63 ], [ 73 ], [ 74 ], [ 75 ], [ 76 ] [ 77 ], [ 78 ], [ 79 ], [ 80 ],. [ 81 ], [ 82 ], [ 83 ], [ 84 ], [ 85 ], [ 86 ], [ 87 ], [ 88 ], [ 89 ], [ 90 ], [ 91 ], [ 92 ], [ 93 ], [ 94 ], [ 95 ], [ 96 ], [ 97 ], [ 98 ], [ 99 ], [ 100 ], [ 101 ], [ 102 ], [ 178 ], [ 192 ] 363 NR in all articles. In large population studies ischemic stroke was reported in 1% [ 77 ] to 2.5% [ 84 ] of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previously reported series, most of the reported cases ( n = 20; 90.9%) had been diagnosed in males. 3 In terms of the vascular territories, stroke involving the anterior circulation was noted in 13 patients (65%) and in the posterior circulation in 6 patients (27.3%). 3 In addition, stroke as the initial clinical manifestation of COVID-19 was noted in 18 patients (81.8%).…”
Section: Discussionmentioning
confidence: 97%